A review of recent sightings and reports of the giant tiger shrimp Penaeus monodon (Decapoda: Penaeidae) on the Mexican coast of the Gulf of Mexico (2012-2019) - Wakida-Kusunoki, Armando T.; Cruz-Sánchez, José Luis; López-Téllez, Norma Angélica (Revista de Biología Marina y Oceanografía, 2021)
This work shows an update of the sightings and reports of tiger shrimp Penaeus monodon on the Mexican coast of the Gulf of Mexico recorded from 2012 to 2019 and reports the smallest specimen found in the western Atlantic. The results show an increase of almost 300% in sightings and reports since the first report. The zone with most sightings and reports was the coast of Campeche and Yucatán. The wide range of size and distribution of the captured specimens, including the smallest specimen found in the western Atlantic and the presence of females at an advanced stage of gonadal maturity, indicates that P. monodon has established itself in the area. The possible negative effects of such establishment make necessary the proposal of measures based on scientific evidence.